Data for: Early season mass-flowering crop cover dilutes wild bee abundance and species richness in temperate regions: a quantitative synthesis - Riggi, Laura (Swedish University of Agricultural Sciences, 2023)
The dataset combines 22 datasets from 13 publications conducted in 9 temperate countries (20 European and 2 North American). The data was used to investigate if mass-flowering crop flowering time (early or late season), bloom state (during or after crop flowering) and extent of non-crop habitat cover in the landscape moderated the effect of mass-flowering crop cover on wild pollinator abundance and species richness in mass-flowering crop and non-crop habitats.
The dataset include the following files: SNHds_final (16 variables, 583 Rows) which included the data for non-crop habitat analyses and, MFCds_final (15 variables, 348 Rows) which includes the data for mass-flowering crop habitat analyses.

Datauppsättningen kombinerar 22 dataset från 13 publikationer utförda i 9 tempererade länder (20 europeiska och 2 nordamerikanska). Data användes för att undersöka om massblommande grödas blomningstid (tidig eller sen säsong), blomningstillstånd (under eller efter grödans blomning) och omfattningen av icke-gröda habitattäckning i landskapet modererade effekten av massblommande grödtäckning på vilda pollinerare överflöd och artrikedom i massblommande grödor och icke-grödor livsmiljöer.
Datauppsättningen innehåller följande filer: SNHds_final (16 variabler, 583 rader) som inkluderade data för habitatanalyser för icke-grödor och MFCds_final (15 variabler, 348 rader) som inkluderar data för massblommande växtmiljöanalyser.
Data för: Tidig säsongs massblommande grödtäckning späder ut vilda bins abundans och artrikedom i tempererade områden: en kvantitativ syntes
Keywords: landscape research; landskapsforskning; pollinators; pollinerare; landscape management; landskapsvård; insecta; diptera; hymenoptera; Seasonal effects; Säsongseffekter; Floral resource; Blommig resurs; Pollinator abundance; Pollinatoröverflöd; Pollinator richness; Pollinatorrikedom; Dilution effects; Utspädningseffekter; Landscape composition; Landskapskomposition; Mass-flowering crops; Massblommande grödor; Ecology; Ekologi; Biota; Biologi och ekologi